Efficient numerical algorithms for balanced stochastic truncation - Benner, Peter; Quintana-Ortí, Enrique S.; Quintana-Ortí, Gregorio (Zielona Góra: Uniwersytet Zielonogórski)
We propose an efficient numerical algorithm for relative error model reduction based on balanced stochastic truncation. The method uses full-rank factors of the Gramians to be balanced versus each other and exploits the fact that for large-scale systems these Gramians are often of low numerical rank. We use the easy-to-parallelize sign function method as the major computational tool in determining these full-rank factors and demonstrate the numerical performance of the suggested implementation of balanced stochastic truncation model reduction.
Keywords: model reduction; stochastic realization; balanced truncation; sign function method; Newton's method